UPAYA PERLINDUNGAN SUMBER DAYA GENETIK BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2016 TENTANG PATEN - Masrur, Devica Rully (Muhammadiyah University Press, 2018)
AbstractThe use of genetic resources in several countries is currently increasing. However, the theft of genetic resources and/or traditional knowledge for commercial purposes (biopircay) and misuse of genetic resources (misappropriation) are also increasing. The Intellectual Property Rights regime, specifically Patents and Plant Variety Protection does not provide sufficient protection for genetic resources and traditional knowledge. Convention on Biological Diversity (CBD) 1992 provided opportunity for regulating the protection of biological resources that had begun to become extinct because they were used freely by world pharmaceutical companies. Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization to the CBD 2010 and FAO International Treaty on Plant Genetic Resources for Food and Agriculture (ITPRFA) 2004 provide provisions regarding access to genetic resources carried out based on mutually agreed terms, prior informed consent dan fair and equitable of benefit sharing. Indonesia has ratified various international agreements relating to access to genetic resources and currently Indonesia has Law Number 13 of 2016 concerning Patent which also regulates that Indonesia's genetic resources are protected. The presence of Law Number 13 of 2016 concerning Patent complements the Indonesian government's efforts to save genetic resources from biopiracy and misappropriation. With various national policies at this moment, we can analyze appropriate efforts to strengthen the protection of genetic resources in Indonesia by continuing to open cooperation with foreign parties to jointly utilize Indonesia's genetic resources with fair benefit sharing.